Design of the shafts of a driven conveyor as part of a mobile working machine modification - Miroslav Blatnický; Ján Dižo; Alyona Lovska; Oleksandr Kravchenko (Acta Technica Jaurinensis)
The purchase of professional technical equipment for processing wooden logs does not always mean the trouble-free processing of a product. One such case is the mobile working machine solved in this research. There was found insufficient semi-automation of processes, technical documentation that did not correspond to the actual state, the need for tremendous effort from the operating personnel, the complete inoperability of some processes and the manufacturer's inability to solve the deficiencies of the machine. These are the reasons and motivations for the creation of the presented applied research, dealing mainly with the elimination of the aforementioned shortcomings. Commonly available and offered peripherals and accessories for the machine are not compatible, and therefore, the authors decided to implement their design to significantly improve the given state. At the same time, the results can be helpful in creating improvement designs for the technical equipment in question for a variety of manufacturers. The main of the given research is to design a driven conveyor of the machine. It is a specifically adapted chain conveyor as the input part of the machine.